Integration of filter-less unified power quality conditioner (UPQC) control scheme with solar photovoltaic and battery energy storage system / Muhammad Alif Mansor - Mansor, Muhammad Alif (2023)
The amalgamation of existing Distribution Generation (DG) with Energy Storage Systems (ESS), Renewable Energy (RE), and Electric Vehicle to Grid (V2G) will increase concerns about power quality issues because of the present complexity of power electronic interfaces in an existing grid distribution. To ensure high power quality and reliability on the grid distribution, a unified power quality conditioner (UPQC) is a useful device for these issues. UPQC can mitigate these power quality issues by injecting appropriate voltages and currents to compensate for the disturbances in real-time, especially the harmonics penetrated by the non-linear loads. The one of most used time-domain methods in the UPQC control scheme is the synchronous reference frame (SRF). However, some drawback exists in this traditional SRF method they involve a phase lock loop (PLL) for reference signal extraction, which can cause large amplitude and phase errors and, as a result, can lead to poor voltages and currents compensation. This problem causes sluggish transient response and high overshoots, hence will impact the system stability. In this study, the proposed Filter-Less with Synchronous Reference Framework (FL-SRF) is used in the UPQC control scheme to enhance power quality at the Point of Common Coupling (PCC) under adverse voltage source problems condition (unbalanced and distorted source voltage). Fundamentally, the traditional SRF control scheme is modified with integrates the filter-less concept that had two main parts which are the phase estimator synchronization technique (FL-PES) and harmonic extractor (FL-HE). The FL-PES is used to produce the synchronization phases reference which can lead to UPQC controller generated reference current and voltage in phase with the operating power system. Therefore, in this case, a PLL necessity is omitted. This technique compared to PLL is less complex mathematical calculations, fast response, does not introduce any phase delay, and has better filtration ability. Meanwhile, the FL-HE is also used to extract the unwanted harmonic produced by the non-linear load. The suggested FL-SRF technique is compared with the traditional SRF technique by considering several case scenarios of source voltage in MATLAB-Simulink software are discussed in detail. Furthermore, the UPQC is supported by the solar Photovoltaic (PV) and Battery Energy Storage System (BESS) in this study. Generally, the PV system supplies the active power to the load. However, once the PV is unable to supply the power, then the BESS activates and provides power, especially during longer-term voltage interruption. The standalone PV system is less reliable compared to a hybrid PV-BESS system because of its instability and high environmental dependency. Results revealed that the PV-BESS-UPQC will improve the voltage support capability continuously in the longer-term grid discontinuity, reduce the complexity of the DC-link voltage regulation algorithm, keep producing clean energy, and inject power back to the grid, especially for critical loads such as semiconductor industries, hospitals, etc.